2006
DOI: 10.1063/1.2192519
|View full text |Cite
|
Sign up to set email alerts
|

Infrared absorptions of NH3(H2) complexes trapped in solid neon

Abstract: When a very small concentration of H2 is added to a Ne:NH3=800:1 sample and the resulting mixture is deposited at 4.3 K, a new absorption appears at 4151.1 cm(-1) which can be assigned to the H2 stretching fundamental of H2 (j=1) complexed with NH3. Other new absorptions which appear near the vibrational fundamentals of NH3 are assigned to the NH3 moiety in this complex and in the complex of NH3 with H2 (j=0). The results of experiments in which HD or D2 is added to the Ne:NH3 mixture support these assignments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…71 Further, the oH 2 molecule in this complex "exhibits a relatively prominent infrared absorption". 71 Therefore, we ascribe the anomalously large splitting between the ortho-NH 3 -induced Q 1 (0) and Q 1 (1) features and the prominent ortho-NH 3induced Q 1 (1) features to a strong intermolecular interaction between oH 2 and ortho-NH 3 .…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…71 Further, the oH 2 molecule in this complex "exhibits a relatively prominent infrared absorption". 71 Therefore, we ascribe the anomalously large splitting between the ortho-NH 3 -induced Q 1 (0) and Q 1 (1) features and the prominent ortho-NH 3induced Q 1 (1) features to a strong intermolecular interaction between oH 2 and ortho-NH 3 .…”
Section: Resultsmentioning
confidence: 91%
“…71 That matrix isolation study reported that oH 2 −NH 3 complexes readily form where it is believed the H 2 coordinates with the lone-pair electrons on the NH 3 molecule to form a complex in which the H 2 bond axis is aligned along the 3-fold symmetry axis of the NH 3 . 71 Further, the oH 2 molecule in this complex "exhibits a relatively prominent infrared absorption". 71 Therefore, we ascribe the anomalously large splitting between the ortho-NH 3 -induced Q 1 (0) and Q 1 (1) features and the prominent ortho-NH 3induced Q 1 (1) features to a strong intermolecular interaction between oH 2 and ortho-NH 3 .…”
Section: Resultsmentioning
confidence: 99%
“…The dynamics of the gas-phase collisions of the species involved strongly depends on important features of the multidimensional intermolecular potential energy surfaces (PES), such as barriers, anisotropies, binding energy, and structure in the most stable configurations. Moreover, detailed knowledge of the features of the PES, in particular, in the long-range region, and of the balance of the various interaction components is important to cast light on the origin, strength, and selectivity of the weak intermolecular hydrogen bond. In particular, it is important to assess if ammonia, as observed for water, ,, may show in embryo a stereoselective Lewis acid–basic character when interacting with H 2 . A large number of studies can be found in the literature (see, for instance, refs , , ), providing information on H 2 O–H 2 or NH 3 –H 2 , although detailed experimental characterizations are scarce. Herein, we propose for the first time a direct experimental comparison of these two prototype systems, carried out by molecular beam scattering under identical conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of nuclear spin isomers in both partners in the complex leads to highly specific symmetry constraints. Matrix isolation studies 4,5 and gas phase studies [6][7][8] of H 2 containing complexes indicate a significant influence of the rotational state of H 2 for complex formation which leads to marked differences between o−H 2 and p−H 2 .…”
Section: Introductionmentioning
confidence: 99%